Enlarged Area of Mesencephalic Iron Deposits in Adults Who Stutter - Liman, Jan; Wolff von Gudenberg, Alexander; Baehr, Mathias; Paulus, Walter; Neef, Nicole E.; Sommer, Martin (Frontiers in Human Neuroscience, 2021)
Purpose Childhood onset speech fluency disorder (stuttering) is possibly related to dopaminergic dysfunction. Mesencephalic hyperechogenicity (ME) detected by transcranial ultrasound (TCS) might be seen as an indirect marker of dopaminergic dysfunction. We here determined whether adults who stutter since childhood (AWS) show ME. Methods We performed TCS in ten AWS and ten matched adults who never stuttered. We also assessed motor performance in finger tapping and in the 25 Foot Walking test. Results Compared to controls, AWS showed enlarged ME on either side. Finger tapping was slower in AWS. Walking cadence, i.e., the ratio of number of steps by time, tended to be higher in AWS than in control participants. Discussion The results demonstrate a motor deficit in AWS linked to dopaminergic dysfunction and extending beyond speech. Since iron deposits evolve in childhood and shrink thereafter, ME might serve as an easily quantifiable biomarker helping to predict the risk of persistency in children who stutter.